2016
DOI: 10.1001/jamapsychiatry.2016.0109
|View full text |Cite
|
Sign up to set email alerts
|

Hydromorphone Compared With Diacetylmorphine for Long-term Opioid Dependence

Abstract: IMPORTANCE Diacetylmorphine hydrochloride (the active ingredient in heroin), delivered under supervision, is effective for the treatment of severe opioid use disorder. However, owing to political and regulatory barriers, it is not available in many settings around the world, which limits the options for many long-term street opioid injectors not attracted into or retained in available treatments. OBJECTIVE To test if injectable hydromorphone hydrochloride is noninferior to injectable diacetylmorphine in reduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
165
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(170 citation statements)
references
References 36 publications
2
165
1
2
Order By: Relevance
“…The within‐trial analysis considers strategies from the SALOME study, a 6‐month, Phase III, double‐blind, non‐inferiority trial in which 202 patients with severe opioid use disorder in Vancouver (Canada) were assigned randomly to either injectable HDM (average daily dose = 261 mg) or DAM . The trial found that self‐reported days of street heroin use was non‐inferior for the per protocol analysis −1.44 days different; 90% confidence interval (CI) = −3.22, 0.27 (marginally different for the ITT analysis −2.34, 90% CI = − 4.14, −0.52), as well as days of non‐prescribed opioid use and urinalysis positive to illicit heroin markers [both non‐inferior per protocol and intention‐to‐treat (ITT)].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The within‐trial analysis considers strategies from the SALOME study, a 6‐month, Phase III, double‐blind, non‐inferiority trial in which 202 patients with severe opioid use disorder in Vancouver (Canada) were assigned randomly to either injectable HDM (average daily dose = 261 mg) or DAM . The trial found that self‐reported days of street heroin use was non‐inferior for the per protocol analysis −1.44 days different; 90% confidence interval (CI) = −3.22, 0.27 (marginally different for the ITT analysis −2.34, 90% CI = − 4.14, −0.52), as well as days of non‐prescribed opioid use and urinalysis positive to illicit heroin markers [both non‐inferior per protocol and intention‐to‐treat (ITT)].…”
Section: Methodsmentioning
confidence: 99%
“…Despite this, medically prescribed DAM is not available in Canada without special access due to regulatory and political reasons . In the quest to find a more politically acceptable alternative to DAM, the Study to Assess Long‐term Opioid Maintenance Effectiveness (SALOME) trial was conducted to test if injectable hydromorphone (HDM) was non‐inferior to injectable DAM as a second‐line treatment for severe opioid use disorder . HDM is currently licensed for moderate to severe pain treatment but at smaller doses than utilized in the SALOME trial for treatment of opiate dependence.…”
Section: Introductionmentioning
confidence: 99%
“…prescription heroin) administered under medical supervision was more efficacious than oral methadone for engagement in treatment (Oviedo-Joekes et al, 2009). A follow-up study found that injectable hydromorphone was as effective as injectable diacetylmorphine (Oviedo-Joekes et al, 2016), making this therapy an option in jurisdictions where diacetylmorphine faces legal hurdles to prescribing.…”
Section: Overdose Response In the Synthetic Opioid Eramentioning
confidence: 99%
“…Six randomized controlled trials have demonstrated that injectable diacetylmorphine (heroin) given under medical supervision is superior to methadone for retaining such patients in addiction treatment and decreasing the use of non-prescribed heroin [5]. Furthermore, a recent non-inferiority study demonstrated that injection hydromorphone had similar results to diacetylmorphine [6]. These studies have been conducted over several months and in outpatient settings.…”
Section: Introductionmentioning
confidence: 99%